Sifat-Sifat Kuantitatif dan Jarak Genetik Kerbau Lokal Sulawesi Tenggara Berdasarkan Pendekatan Morfologi - Muh. Rusdin; Dedi Duryadi Solihin; Asep Gunawan; Chalid Talib; Cece Sumantri (Jurnal Ilmu Pertanian Indonesia, 2018)
Information on animal genetic resource is needed in conservation program of Indonesian local buffalo. This study was aimed to analyze the quantitative traits diversity and genetic distance of local buffalo of Southeast Sulawesi local based on morphological approach. The total of 271 heads of swamp buffaloes were used in the study from four sub-populations, namely Bombana island’s, Bombana mainland, Kolaka and Konawe. Duncan Multiple Range test at 5% probability was used to compare the quantitative traits between the buffalo sub-populations. Genetic distance was analyzed by using the simple discriminant function. The results showed that the average body weight of male buffalo between sub-populations was not significantly different (P>0.05), but the average body weight of females buffalo from Bombana Island’s (465.22 ± 103.25) was significantly (P<0.05) higher than those of the other sub-populations. The highest variation of quantitative traits of local buffalo was found in Konawe sub-population, i.e. in body weight of female buffalo (35.36%) and body weight of male buffalo (22.05%), rump length in males buffalo (20.44%), and rump width in females buffalo (14.58%). Southeast Sulawesi local buffalo can be grouped into three clusters based on the phylogeny tree, namely 1) Kolaka and Konawe cluster, 2) Bombana island’s cluster, and 3) Bombana mainland cluster. The distinguishing variables of the group of Southeast Sulawesi local buffalo were rump length, body length, and chest circumference. The highest phenotype similarity value was shown by Bombana island’s buffalo (68.57%), while the lowest was found at Konawe buffalo (26.76%). The farthest genetic distance was found between Bombana Islands and Konawe buffalo (3.71703), while the closest genetics distance was identified between Kolaka and Konawe buffalo (0.86616).